Development of innovative catalysts for the hydrodechlorination to fluoroethers - Gregori, Manuel <1981> (Alma Mater Studiorum - Università di Bologna, 2014)
In this work the hydrodechlorination of CF3OCFClCF2Cl to produce unsaturated CF3OCF=CF2 was studied over a series of supported metal catalysts. Currently this molecule is produced from the precursor CF3OCFClCF2Cl by dechlorination with zinc powder. An important cost on the economic and environmental balance is represents by the large amount of ZnCl2 produced and to be disposed of. A new approach, based on gas-phase hydrodechlorination over supported catalysts can lead to a new sustainable process. During the feasibility step of this project, substantially two kind of materials were studied: metals supported over activated carbon and Pd/Cu species supported over MCM-41 mesoporous silica. Observed catalytic performances were strongly dependent on the metal and support used. All carbon-supported Ru, Pd, and bimetallic catalysts are fairly active and yielded the target product CF3OCF=CF2, the higher selectivity being obtained with ruthenium- and palladium-based materials. Nevertheless, Ru-based catalysts showed poor stability and this deactivation may be attributed to the deposition of chlorinated organic species blocking the active sites. On the other hand, palladium-containing catalysts showed high stability. Ru/Pd and Pd/Cu bimetallic catalysts exhibited long-term selectivity and stability, highlighting the possibility for these materials to be employed in the CF3OCF=CF2 production process. During the second part of this thesis, a series of bimetallic meso-structured Pd/Cu MCM-41 catalysts were studies to overcome possible mass transfer limitations. The materials were obtained by different synthesis methods. The incorporation of Pd and Cu during MCM-41 synthesis, did not destroy the typical hexagonal array and ordered pore system of MCM-41. However, the calcination for the removal of the template provoked significant segregation of oxides. The impregnation leads to pore-occlusion and formation of Cu particles and large bimetallic PdCu species. Larger metal particles leads to lower CF3OCFClCF2Cl conversion, while the monometallic particles can decrease the selectivity to CF3OCF=CF2, fostering the dehalogenation to CF3OCH=CF2.